2014
DOI: 10.3324/haematol.2013.096792
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between comorbidity and treatment of chronic lymphocytic leukemia: results of German Chronic Lymphocytic Leukemia Study Group trials

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nthis on-site documentation, causes of death were grouped into the following categories: therapy-related, CLL-related, CLL-unrelated, or unknown. Both studies were approved by the Institutional Review Board and Ethics Committee of the University of Munich and performed in accordance with the Declaration of Helsinki. Comorbidity assessmentFor both trials, comorbid conditions present at baseline had to be assessed and documented in the patient's case report form by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 23 publications
4
79
0
5
Order By: Relevance
“…13 However, we detected a relationship between overall response rate and comorbidity at time of treatment (CIRS-T), which is in line with other studies. 18,19 A moderate to severe comorbidity burden (CIRS-D >6 and CIRS-T >4) was strongly associated with shorter overall survival. Of note, the cutoff that better correlated with overall survival (CIRS-T >4) was different from that in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 However, we detected a relationship between overall response rate and comorbidity at time of treatment (CIRS-T), which is in line with other studies. 18,19 A moderate to severe comorbidity burden (CIRS-D >6 and CIRS-T >4) was strongly associated with shorter overall survival. Of note, the cutoff that better correlated with overall survival (CIRS-T >4) was different from that in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] In a pooled analysis comprising 555 patients comorbidity had an independent impact on overall survival (71.7 versus 90.2 months; P<0.001) due to higher therapy-related, CLL-unrelated, and, particularly, CLL-related deaths. 19 In the present study we assessed comorbidity by CIRS 12,13 at diagnosis (CIRS-D) and prior to first treatment (CIRS-T). No correlation was found between comorbidity and performance status, which is in agreement with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found an association between comorbidities and survival in CLL, although renal function was either not included or not analyzed individually in these reports. 8,9 Our data reveal that RI appears to have an independent prognostic role in patients with CLL. Given this, we would propose that the impact of RI as a prognostic comorbid feature warrants validation in prospective studies, along with other previously recognized comorbidities.…”
Section: P<0001mentioning
confidence: 76%
“…Looking at the different items in terms of number and severity, it appeared that 5-year mortality was 40% for patients with more than 2 co-morbidities, compared to 25% for those with less than 2 co-morbidities. 19 Among the various scales of the CGA, a co-morbidity index (CIRS) has been correlated with overall survival and is currently used as a decision tool for inclusion in German CLL trials. Data from the CLL8 trial (n=817), where patients were randomized between FCR and FC and where CIRS was mandatory (exclusion if CIRS >6), showed that a CIRS Editorials score over 3 in this selected population was a prognostic factor correlated with OS independent of age, ECOG status and other CLL prognostic factors.…”
Section: The Role Of Immune Senescence In the Development Of Cancermentioning
confidence: 99%